Safety evaluation of the food enzyme β‐fructofuranosidase from the non‐genetically modified Saccharomyces cerevisiae strain CNCM I‐3399 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme β‐fructofuranosidase (β‐d‐fructofuranoside fructohydrolase; EC 3.2.1.26) is produced with the non‐genetically modified Saccharomyces cerevisiae strain CNCM I‐3399 by Kerry Ingredients & Flavours Ltd. The production strain qualifies for the qualified presumption of safety (QPS) approach for risk assessment. The food enzyme is intended to be used in four food manufacturing processes. Exposure was estimated to be up to 2.485 mg total organic solids/kg body weight (bw) per day in European populations. As the production strain qualifies for QPS, and in the absence of other concerns, the Panel considered that toxicological studies were not needed for the safety assessment of this food enzyme. A search for homology of the amino acid sequence of the food enzyme to known allergens was made and one match with a tomato allergen was found. The Panel considered that the risk of allergic reactions upon dietary exposure to this food enzyme, particularly in tomato allergic individuals, cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.